Investigation of cultivated lavender (Lavandula officinalis L.) extraction and its extracts - Nađalin Vesna (Chemical Industry and Chemical Engineering Quarterly, 2014)
In this study essential oil content was determined in lavender flowers and leaves by hydrodistillation. Physical and chemical characteristics of the isolated oils were determined. By using CO2 in supercritical state the extraction of lavender flowers was performed with a selected solvent flow under isothermal and isobaric conditions. By the usage of gas chromatography in combination with mass spectrometry (GC/MS) and gas chromatography with flame ionisation detector (GC/FID) the qualitative and quantitative analysis of the obtained essential oil and supercritical extracts (SFE) was carried out. Also, the analysis of individual SFE extracts obtained during different extraction times was performed. It turned out that the main components of the analysed samples were linalool, linalool acetate, lavandulol, caryophyllene oxide, lavandulyl acetate, terpinen-4-ol and others. Two proposed models were used for modelling the extraction system lavender flower - supercritical CO2 on the basis of experimental results obtained by examining the extraction kinetics of this system. The applied models fitted well with the experimental results.